Zoledronic Acid and Its Accentuating Effect on Tumor Radiosensitivity. (11th July 2013) - Kapoor, Shailendra
Abstract : Recent data suggest that zoledronic acid may significantly augment the radiosensitivity of a number of systemic malignancies, including fibrosarcomas. Oncologists need to be aware of the radiosensitivity‐enhancing properties of zoledronic acid.